Construction scheme analysis of computing force network - Lili WANG (Dianxin kexue)
The government puts forward higher requirements for the deployment of computing force network (CFN), so the telecom operators accelerate the implementation of computing network integration.Aiming to solve the problems of computing and network coordination and scheduling, based on the study of standards related to CFN, the research progress of CFN was summarized, the business requirements of CFN were analyzed, combined with the current reality of telecom operators, the deployment scheme of sustainable construction of CFN was put forward, which concerned with computing power reserve, transmission network, network routing and intelligent scheduling, it provides a reference for the early stage of CFN construction.